1983
DOI: 10.1104/pp.71.3.598
|View full text |Cite
|
Sign up to set email alerts
|

Redox Reactions between Kaempferol and Illuminated Chloroplasts

Abstract: MATERIALS AND METHODSBleaching of kaempferol by iUluminated chloroplasts was observed at 380 nanometers. The photobleaching was stimulated by methyl viologen and suppressed by superoxide dismutase indicating the participation of 02-in the reaction. An electron transfer inhibitor on the oxidizing side of photosystem 11, carbonylcyanide m-chlorophenylhydrazone (CCCP), stimulated the photobleaching and 3-(3,4-dichlorophenyl)-1,1-dinethylurea partially suppressed it. The stimulation by CCCP suggests that kaempfero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0
1

Year Published

1984
1984
2010
2010

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 12 publications
0
28
0
1
Order By: Relevance
“…These codominant genes code for the addition of (2,27), we suspected that K9 might also be inhibitory in vivo. In an attempt to circumvent the problem of flavonoid contamination during chloroplast isolation (see "Introduction"), we examined whole mesophyll cells from soybeans to determine if the kaempferol glycosides, especially K9, were present in this photosynthetic tissue.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These codominant genes code for the addition of (2,27), we suspected that K9 might also be inhibitory in vivo. In an attempt to circumvent the problem of flavonoid contamination during chloroplast isolation (see "Introduction"), we examined whole mesophyll cells from soybeans to determine if the kaempferol glycosides, especially K9, were present in this photosynthetic tissue.…”
Section: Discussionmentioning
confidence: 97%
“…The inhibitory effects of kaempferol aglycone on photosynthesis in vitro are well characterized (2,27), but its glycosides are less effective (2). There are reports that flavonoid glycosides occur in plastids isolated from several species (19,26,28,29) including soybean (26), but it is difficult to rule out plastid contamination by vacuolar flavonoids during subcellular fractionation.…”
mentioning
confidence: 99%
“…The enhancement of H 2 O 2 production is possible by the stimulation of leukocytes in the oral cavity. H 2 O 2 formation usually accompanies the formation of O 2 -and it is known that flavonol aglycones like kaempferol and quercetin reduce O 2 -to H 2 O 2 (Takahama 1983(Takahama , 1987Bors et al, 1997).…”
Section: Salivary Polymorphonuclear Leukocytes (Spmn) Produce Omentioning
confidence: 99%
“…The enhancement of H 2 O 2 production is possible by the stimulation of leukocytes in the oral cavity. H 2 O 2 formation usually accompanies the formation of O 2 -and it is known that flavonol aglycones like kaempferol and quercetin reduce O 2 -to H 2 O 2 (Takahama 1983(Takahama , 1987Bors et al, 1997).Blackburn Jr. et al (1987) reported that quercetin can inhibit O 2 -production, degranulation and phosphorylation of specific proteins, which are observed in plasma neutrophils when stimulated.…”
mentioning
confidence: 99%
“…5). It has already been reported that quercetin was oxidized by O2 and radicals formed during lipid peroxidation and that the oxidation was accompanied by the absorbance decrease at 380 nm (19,20 …”
mentioning
confidence: 99%